2015
DOI: 10.1098/rspb.2014.2336
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bottom trawling on fish foraging and feeding

Abstract: The effects of bottom trawling on benthic invertebrates include reductions of biomass, diversity and body size. These changes may negatively affect prey availability for demersal fishes, potentially leading to reduced food intake, body condition and yield of fishes in chronically trawled areas. Here, the effect of trawling on the prey availability and diet of two commercially important flatfish species, plaice (Pleuronectes platessa) and dab (Limanda limanda), was investigated over a trawling intensity gradien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 49 publications
(89 reference statements)
2
41
1
Order By: Relevance
“…In relation to trawl intensity the two species showed a highly opportunistic feeding strategy and co-occurred at all sites by showing differences in their diet preferences (Ribi et al, 1977) and shifting in size-frequency distributions. Our results support the hypothesis that bottom trawling affects the fitness of benthivorous organisms by altering the food availability and generating a positive response of facultative scavengers to carrion (Demestre et al, 2000;Link, 2004;Dell et al, 2013;Johnson et al, 2015).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In relation to trawl intensity the two species showed a highly opportunistic feeding strategy and co-occurred at all sites by showing differences in their diet preferences (Ribi et al, 1977) and shifting in size-frequency distributions. Our results support the hypothesis that bottom trawling affects the fitness of benthivorous organisms by altering the food availability and generating a positive response of facultative scavengers to carrion (Demestre et al, 2000;Link, 2004;Dell et al, 2013;Johnson et al, 2015).…”
Section: Discussionsupporting
confidence: 79%
“…Here, we tested the hypothesis that bottom trawling affects the diet of benthivorous organisms by altering food availability and generating a positive response of facultative scavengers to carrion. Benthic scavengers feeding on the benthic community that results from the effects of trawling might represent costeffective samplers, hence diet studies may provide insights into the trophic consequences of such community changes for other components of the ecosystem (Link, 2004;Dell et al, 2013;Johnson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Bottom trawl fisheries affect populations of commercial species, such as flatfish and crustaceans, directly by harvesting, or indirectly through physical habitat changes induced by mechanical trawl equipment leading to population changes in benthic invertebrates on which these benthivorous species feed 35 . So far most studies on bottom trawling have examined these direct and indirect effects separately.…”
Section: Introductionmentioning
confidence: 99%
“…; Johnson et al . ). Modelling studies of the effects of bottom trawling on fish feeding (Hiddink et al .…”
Section: Discussionmentioning
confidence: 97%
“…The most insightful study to date is that of Johnson et al . () who showed that flatfish were able to maintain their stomach fullness despite the reduction in local prey biomass and abundance. However, these fish had reduced body condition, which is most likely explained by the additional energetic costs of searching for food in a reduced prey field.…”
Section: Introductionmentioning
confidence: 99%